2021
DOI: 10.3390/ijerph19010254
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Usage and Resistance in Makkah Region Hospitals: A Regional Point Prevalence Survey of Public Hospitals

Abstract: (1) Background: Inappropriate use of antimicrobials and subsequently rise of antimicrobial resistance (AMR) remains a major public health priority. Over-prescribing of broad-spectrum antibiotics is one of the main contributing factors for the emergence of AMR. We sought to describe antimicrobial prescribing trends among patients in public hospitals in Makkah hospitals. (2) Method: We undertook a point prevalence survey (PPS) in six hospitals in Makkah, Saudi Arabia, from January 2019 to July 2019. The survey i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…Twenty-six of the 51 papers reported the results of AMR-related research conducted in hospital settings [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] while eight were case reports [ 31 , 38 , 40 , 41 , 53 , 54 , 55 , 56 ]. One was an outbreak report [ 21 ], one hospital-based case-control study [ 45 ], and one article was an environmental to detect AMR in Makkah [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-six of the 51 papers reported the results of AMR-related research conducted in hospital settings [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] while eight were case reports [ 31 , 38 , 40 , 41 , 53 , 54 , 55 , 56 ]. One was an outbreak report [ 21 ], one hospital-based case-control study [ 45 ], and one article was an environmental to detect AMR in Makkah [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the respiratory disease-causing AMR bacteria: Staphylococcus spp. in 17 studies [ 28 , 30 , 33 , 36 , 37 , 42 , 43 , 48 , 52 , 55 , 57 , 61 , 63 , 64 , 67 , 68 , 69 ], Streptococcus spp. in seven study [ 33 , 42 , 65 , 70 , 71 , 72 , 73 ], Neisseria meningitidis in three studies [ 21 , 22 , 54 ], Haemophilus influenzae was reported in two studies [ 27 , 32 ], Mycobacterium tuberculosis in two studies [ 74 , 75 ], and Stenotrophomonas maltophilia in one study [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Antimicrobials were administered parenterally to the vast majority of patients (90.3%). About 53.7% of the total antimicrobials prescriptions were utilized in medical departments, 23.7% in surgical departments, and 22.6% in intensive care units (Haseeb et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Although highly recommended by the healthcare community, prophylactic drugs are included in the crucial immunosuppressive regimen, resulting in considerable economic burden for the immunocompromised patients [ 38 ]. Routine PCP prophylaxis is recommended for patients treated in hospitals where the prevalence of PCP is at least 3% to 5% among immunocompromised patients [ 12 , 39 , 40 ]. Moreover, the risk of PCP among transplant recipients is greater in 1–6 month post-transplantation period, during prolonged neutropenia, or in patients receiving steroids, antilymphocyte antibodies, or calcineurin inhibitors [ 41 ].…”
Section: Discussionmentioning
confidence: 99%